2017
DOI: 10.1007/s11869-017-0464-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five-year observation data of fine particulate matter in the metropolitan area of Lahore

Abstract: This study aims to assess the long-term trend of fine particles (PM2.5; ≤2.5 μm) at two urban sites of Lahore during 2007–2011. These sites represent two distinct areas: commercial (Townhall) and residential cum industrial (Township). The highest daily mean concentrations of PM2.5 were noted as 389 and 354 μg m−3 at the Townhall and Township sites, respectively. As expected, the annual seasonal mean of PM2.5 was about 53 and 101% higher during winter compared with the summer and monsoon/post-monsoon seasons, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…PMD's representative was of view that the impacts of climate change are not as visible in Lahore in a macroscopic view, but the congestion in Lahore is the reason of feeling high temperatures in summers and low temperatures in winter seasons. This viewpoint is also in harmony with observation of the temperature differences in Lahore (Sajjad et al, 2015); yet this is amazingly contrary to the measurements reported by Khanum et al (2017) that the city's annual average of PM2.5 for last five years was 136.5 ± 34.1 μg/m 3 which is alarmingly 14 times higher than WHO guidelines. However, the main reasons identified for the climate change of Lahore were the development and expansion of Lahore, traffic congestion and air pollution and deforestation.…”
Section: Findings and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…PMD's representative was of view that the impacts of climate change are not as visible in Lahore in a macroscopic view, but the congestion in Lahore is the reason of feeling high temperatures in summers and low temperatures in winter seasons. This viewpoint is also in harmony with observation of the temperature differences in Lahore (Sajjad et al, 2015); yet this is amazingly contrary to the measurements reported by Khanum et al (2017) that the city's annual average of PM2.5 for last five years was 136.5 ± 34.1 μg/m 3 which is alarmingly 14 times higher than WHO guidelines. However, the main reasons identified for the climate change of Lahore were the development and expansion of Lahore, traffic congestion and air pollution and deforestation.…”
Section: Findings and Discussionsupporting
confidence: 80%
“…The city experiences extreme weather conditions in both summer (upto 48 o C) and winter (as low as 0 o C) (Rana and Bhatti, 2018). Also, the citizens have been exposed to deadly smog which Lahore has been experiencing as measured by Khanum et. al.…”
Section: Wwweuraasscommentioning
confidence: 99%
“…However, the proposed annual mean levels for the ambient particulate matter, PM 2.5 and PM 10 , were higher than the stricter World Health Organization (WHO) guidelines, which are 10 μg/m 3 and 20 μg/m 3 respectively [ 2 ]. According to data, the levels of the ambient particulate matter reported in Lahore far exceed the recommended values of both WHO guidelines and NEQS guidelines [ 2 , 4 ]. A study conducted in Lahore over a period of 5 years, aiming to compare the level of fine particles with the aforementioned guidelines, concluded that the annual average PM 2.5 of the areas studied was 136.5 ± 34.1 μg/m 3 [ 4 ], which is roughly 14 folds higher than the WHO guidelines.…”
Section: Editorialmentioning
confidence: 99%
“…According to data, the levels of the ambient particulate matter reported in Lahore far exceed the recommended values of both WHO guidelines and NEQS guidelines [ 2 , 4 ]. A study conducted in Lahore over a period of 5 years, aiming to compare the level of fine particles with the aforementioned guidelines, concluded that the annual average PM 2.5 of the areas studied was 136.5 ± 34.1 μg/m 3 [ 4 ], which is roughly 14 folds higher than the WHO guidelines. This study also mentions that this level of particulate matter was comparable to one of the most polluted megacities of the world, Delhi, at 143.0 ± 17.8 μg/m 3 [ 4 ].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation